Indexing in digital repositories: an incursion in the Brazilian scientific production on Information Science - Dal Evedove Tartarotti, Roberta Cristina; Dal'Evedove, Paula Regina [UNESP]; Lopes Fujita, Mariangela Spotti (Univ Zaragoza, 2020)
Subject indexing in digital repositories is surveyed in the Brazilian scientific production of Information Science. In conclusion, it is verified that although the upward relevance of digital repositories, and more presently of the institutional repositories, is currently a reality in the academic field, research in the field of Knowledge Organization that specifically cover the subject indexing in digital repositories are still incipient.
Keywords: Subject indexing; Digital repositories; Scientific production; Information Science; Brazil